2010
DOI: 10.1248/bpb.33.1443
|View full text |Cite
|
Sign up to set email alerts
|

Human Intestinal Bacterium, Strain END-2 Is Responsible for Demethylation as Well as Lactonization during Plant Lignan Metabolism

Abstract: Plant lignans and isoflavones that have estrogen-like properties, are classified as phytoestrogens based on their activities and chemical structures.1,2) Experimental and epidemiological studies have shown that phytoestrogens have potential health benefits in treating hormone-dependent diseases such as breast and prostate cancers. 3-7)Because ingested plant lignans undergo metabolic degradation, their transformation and metabolites have been extensively studied. [8][9][10][11][12][13] The mammalian lignans, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…We found that microbial diversity was significantly different (Simpson Index, p<0.05) between high and low ENL excreters and was positively associated with fiber intake. The association between ENL excretion and microbial diversity may reflect the complexity of the microbial metabolism involved in ENL metabolism since there are several transformations involved in the production of enterolignans from lignans and different bacteria species can catalyze each step (1517, 6668). In a recent study comparing human populations consuming either a western diet or a rural sub-Saharan traditional diet, dietary fiber intake was also associated with gut microbial diversity (69).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that microbial diversity was significantly different (Simpson Index, p<0.05) between high and low ENL excreters and was positively associated with fiber intake. The association between ENL excretion and microbial diversity may reflect the complexity of the microbial metabolism involved in ENL metabolism since there are several transformations involved in the production of enterolignans from lignans and different bacteria species can catalyze each step (1517, 6668). In a recent study comparing human populations consuming either a western diet or a rural sub-Saharan traditional diet, dietary fiber intake was also associated with gut microbial diversity (69).…”
Section: Discussionmentioning
confidence: 99%
“…For example, isolated Eggerthella lenta cannot reduce SECO; however, it can dehydroxylate 2, 3-bis-(3, 4-dihydroxy-benzyl) butane-1, 4-diol to END, one of the intermediary steps in ENL production (12, 15). END can then be converted to ENL by different bacteria (16, 17). Several more bacterial groups likely play similarly unique and complex biochemical roles in the transformation of plant lignans to enterolignans (16).…”
Section: Introductionmentioning
confidence: 99%
“…These compounds are not directly bioavailable and require metabolic steps which involve both mammalian (glucuronidation and to a lesser degree, sulfation) and gut microbial processes [80]. When lignan glycosides are consumed with the diet, they are released from the matrix after mastication, are deglycosylated and are converted in the liver to glucuronidated [81], methylated and sulfated derivatives [82] that can be identified in human urine [83], but also to enterodiol and enterolactone by the intestinal microbiota [20] (Figure 4).…”
Section: Microbial Metabolization Of Lignansmentioning
confidence: 99%
“…The pathway from plant lignan to enterolignans varies between the different types of plant lignans; however, for the majority of the plant lignans, the final step is likely to include dehydrogenation of enterodiol to enterolactone [12]. Bacterial strains capable in catalyzing enterolactone from enterodiol have been identified in studies with human fecal samples and categorized to be subdominant members of the microbiota [13][14][15][16].Production, circulation, and excretion of enterolignans are subject to a substantial interindividual variation [17,18] even in animal experiments with controlled plant lignan intake [19]. A recent study concluded that high excretion of enterolactone, but not enterodiol, is associated with high diversity of the gut microbial community [11].…”
mentioning
confidence: 99%